Safety and efficacy of a feed additive consisting of a tincture derived from the fruit of Pimpinella anisum L. (anise tincture) for use in all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a tincture from the fruit of Pimpinella anisum L. (anise tincture) when used as a sensory additive in feed and water for drinking for all animal species. The product is a ■■■■■ solution, with a dry matter content of approximately 1.6%. The product contained on average 0.0414% polyphenols (of which 0.0144% were flavonoids), 0.0009% anisaldehyde, 0.0003% anethole. Estragole (≤ 1.2 mg/kg) was detected in the additive. The estimated maximum content of furocoumarins was 8.2 mg/kg. The use of the anise tincture in feed was not expected to increase the exposure to furocoumarins of those target species that are already fed citrus by‐products to a relevant extent (< 10%). For dogs, cats and ornamental fish not normally exposed to citrus by‐products, no conclusion could be drawn. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the anise tincture was safe at the maximum proposed use levels in complete feed of 200 mg/kg for horses and 50 mg/kg for poultry, pigs, ruminants, rabbits and salmonids and other fin fish. Anise tincture should be considered as irritant to skin and eyes, and as a dermal and respiratory sensitiser. Since anise tincture may contain furocoumarins, they may cause phototoxicity. When handling the additive, exposure of unprotected users to estragole may occur. Therefore, to reduce the risk, the exposure of the users should be minimised. The use of the anise tincture as a flavour in animal feed was not expected to pose a risk for the environment. Since the fruit of P. anisum and its preparations were recognised to flavour food and their function in feed would be the same, no demonstration of efficacy was necessary.